2014
DOI: 10.1007/s10578-014-0486-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensation Seeking Predicting Growth in Adolescent Problem Behaviors

Abstract: There is limited literature on the relationship between sensation seeking and adolescent risk behaviors, particularly among African Americans. We tested the association between psychometrically-derived subscales of the Zuckerman Sensation Seeking Scale and the intercepts and slopes of individual growth curves of conduct problems, sexual risk taking, and substance use from ages 13-18 years by sex. Boys and girls had different associations between sensation seeking and baseline levels and growth of risk behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
2
19
1
Order By: Relevance
“…Peer (e.g., peer substance use), family (e.g., parental supervision) and individual (e.g., executive control, impulsivity control [27, 33]) factors were not investigated, and therefore it is not known how these factors may contribute to the onset and development of substance use alongside CD symptoms and CU traits. Third, moderating factors such as sensation seeking, impulsivity, risk-seeking, and executive control were not investigated and should be included in future studies to further explore the relationships between CD symptoms, CU traits, and substance use and the mechanisms underlying these relationships [19, 29, 30, 33]. Fourth, in the current study alcohol misuse was operationalized based on self-reports of number of days being drunk and number of days consuming five or more drinks in a row in the past year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer (e.g., peer substance use), family (e.g., parental supervision) and individual (e.g., executive control, impulsivity control [27, 33]) factors were not investigated, and therefore it is not known how these factors may contribute to the onset and development of substance use alongside CD symptoms and CU traits. Third, moderating factors such as sensation seeking, impulsivity, risk-seeking, and executive control were not investigated and should be included in future studies to further explore the relationships between CD symptoms, CU traits, and substance use and the mechanisms underlying these relationships [19, 29, 30, 33]. Fourth, in the current study alcohol misuse was operationalized based on self-reports of number of days being drunk and number of days consuming five or more drinks in a row in the past year.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few factors that may explain the relationship between CU traits and substance use. CU traits are significantly related to impulsivity and sensation seeking among youth [28], which has been related to other problem behaviours such as risky sexual behavior [29]. Further, behaviours such as risk-seeking are more prevalent among this population and may explain the relationship between CU traits and substance use [19].…”
Section: Introductionmentioning
confidence: 99%
“…High sensation-seekers may be more likely to use substances and have multiple sexual partners to fulfill desires for exciting experiences. Traditionally explored with substance use, sensation-seeking is significantly associated with alcohol, cigarette and marijuana use in high school (Byck, Swann, Schalet, Bolland, & Mustanski, 2015;Kong et al, 2013;Voisin, King, Schneider, DiClemente, & Tan, 2012) and CHS youth (Pokhrel, Sussman & Stacy, 2014).…”
Section: Sensation-seeking and Sexual Behaviorsmentioning
confidence: 99%
“…The role of sensation seeking in accounting for this rise in risk-taking behaviour between childhood and adulthood has also been widely discussed (Romer, Reyna, & Satterthwaite, 2017a;Steinberg, 2008). One large cross cultural study has shown that across a number of countries self-reported sensation seeking peaks during adolescence, at 19 years of age, before declining thereafter (Steinberg et al, 2018) and previous work has documented a positive association between sensation seeking, substance use and sexual risk taking (Byck, Swann, Schalet, Bolland, & Mustanski, 2015;Quinn & Harden, 2013;Zhang, Zhang, & Shang, 2016).…”
Section: Current Models Of Adolescent Risk Takingmentioning
confidence: 99%